Contralateral Eye Comparison Between 2 Cap Thicknesses in Small Incision Lenticule Extraction: 110 Versus 130 μm. Issue 5 (May 2019) - Wu, Fang; Yin, Houfa; Yang, Yabo
Abstract : Purpose: To evaluate the posterior corneal elevation (PCE) and biomechanical changes after small incision lenticule extraction (SMILE) at depths of 110 μm and 130 μm. Methods: One hundred sixteen eyes from 58 consecutive patients who underwent SMILE were included in this prospective study. Each patient underwent SMILE in one eye to a depth of 110 μm and in the other eye to a depth of 130 μm. A Scheimpflug camera and Hartmann-Shack WASCA aberrometer were used to assess the PCE and wavefront aberrations, respectively, before SMILE and at 1 and 3 months after surgery. The PCE was analyzed along 3 optical zones (apex and 2 and 4 mm diameters) as a function of the meridian. Dynamic Scheimpflug imaging was used to evaluate the biomechanics preoperatively and at 1 day, 1 month, and 3 months postoperatively. Results: No significant difference was found in either vision correction or corneal biomechanics between the 2 groups. In both groups, the PCE became significantly flattened at the apex and at 2 mm annulus 1 month postoperatively, especially for the 110-μm cap group. Three months postoperatively, the 110-μm cap group was still flattened significantly, whereas the displacement at the apex in the 130-μm cap group had disappeared. There was no significant difference in wavefront aberrations between the groups after surgery, except in the vertical coma ( P < 0.001). Conclusions: The differences in corneal biomechanics between the 110-μm cap group and 130-μm cap group were small; however, the superficial lenticule might cause displacement of the PCE to be more persistent in one eye than in the other.